Three-dimensional elliptical vibration cutting device based on the curved beam. Issue 5 (May 2019) - Lin, Sheng; Deng, Xubiao
Abstract: A novel three-dimensional elliptical vibration cutting device is proposed based on curved beams. Arc curved beam compliant element is employed to synthesize the structure. Static analysis and modal analysis are carried out on the micro-displacement stage. Results show that the maximum stress applied to the device in all three directions is less than the allowable stress. And the first natural frequency of the device is relatively high. The output of the three-dimensional elliptical trajectory is simulated, which meets the requirement.